Cases of Nutritional Adequacy Rates and Strategies for Improving Middle-Aged Elderly Nutrition in Aceh - Safrida S; Diana Mukhlisa; Elvy Mauliza; Nabila Azqia; Ramizatul Fatinah; Siti Aisyah (Journal of Tropical Biodiversity, 2023)
Elderly is one of the processes of a person who has entered the final stage of the life phase. Groups categorized as elderly experience a process called the aging process. The nutritional adequacy rate is the average daily nutritional adequacy. Nutritional adequacy is an indicator of food security at the household level and can be measured by the adequacy of energy, protein and fat. The study aims to analyze the cases of nutritional adequacy of the elderly. The method used a quantitative method using a cross-sectional approach that is complemented by interview techniques using a food recall questionnaire. This study shows that the average level of adequacy of energy, and macronutrients (carbohydrates, protein and fat) is included in the sufficient category, while fiber still needs to be improved, because it is included in the insufficient category. The nutritional status of respondents was mostly normal, although some were in the obese category. to maintain a healthy body, an elderly person needs to do routine activities and have food quality by showing the suitability of food intake based on recommendations, namely the existence of a variety of food groups, nutritional adequacy according to needs, moderation and overall balance.